Accelerated epigenetic age and shortened telomere length based on DNA methylation in Nicolaides–Baraitser syndrome. Issue 3 (29th January 2022) - Shinko, Yutaka; Okazaki, Satoshi; Otsuka, Ikuo; Horai, Tadasu; Kim, Saehyeon; Tanifuji, Takaki; Hishimoto, Akitoyo
Abstract: Background: Nicolaides–Baraitser syndrome (NCBRS) is a rare disorder characterized by neurodevelopmental delays, seizures, and diverse physical characteristics. The DNA methylation (DNAm) profile in NCBRS is significantly different. DNAm is linked to the biological aging of cells and the health risks associated with biological aging. In this study, we examined changes in biological ages in NCBRS to provide insights into the prognosis and health risks of NCBRS. Methods: We used a publicly available dataset to examine biological aging in NCBRS using DNAm‐based epigenetic ages, such as PhenoAge and GrimAge, as well as DNAm‐based estimator of telomere length (DNAmTL). We investigated 12 cases, clinically diagnosed as NCBRS, and 27 controls. Results: Compared to controls, NCBRS cases exhibited significantly accelerated PhenoAge and GrimAge as well as significantly shortened DNAmTL. Conclusion: These results suggest an acceleration of biological aging in NCBRS and provide insights into the prognosis and health risks of NCBRS. Abstract : Nicolaides–Baraitser syndrome (NCBRS) is a rare disorder characterized by neurodevelopmental delays. We examined biological aging in NCBRS and found accelerated epigenetic ages (PhenoAge and GrimAge) and shortened DNA methylation‐based telomere length (DNAmTL) in NCBRS. These results suggest an acceleration of biological aging in NCBRS.